Efektivitas Eco-Enzyme dalam Menurunkan Escherichia coli pada Sendok Makan - Fakhri Dzulfiqar; Nur Hilal; Bahri Bahri (Buletin Keslingmas, 2026)
Eating utensils contaminated with microorganisms can transmit foodborne diseases. Swab results from tablespoons in the Food Court of PKU Muhammadiyah Gombong Hospital showed Escherichia coli contamination of 20 CFU/cm², which did not meet the quality standards. The disinfection stage in the utensil-washing process is rarely practiced due to limited facilities. This study utilized Eco-enzyme, a fermentation product of vegetable and/or fruit waste, as a natural disinfectant. The purpose of this study was to analyze the effectiveness of Eco-enzyme in reducing E. coli counts on tablespoons. This research was a True Experimental study using a Randomized Pretest–Posttest Multiple Treatment Design with 3 treatments: dishwashing soap (1:25 mL), Eco-enzyme (1:10 mL), and a combination of dishwashing soap and Eco-enzyme (1:1:10 mL). Each treatment was applied to 6 tenants, resulting in 18 spoon samples. Data were analyzed using the Wilcoxon test followed by a Kruskal–Wallis and post-hoc Pairwise Comparisons. The Wilcoxon test showed significant differences in E. coli counts before and after treatments (p < 0.05). Post-hoc analysis demonstrated that the Eco-enzyme treatment reduced E. coli more effectively than dishwashing soap (p = 0.008), and the combination treatment was also more effective than dishwashing soap (p = 0.036). No significant difference was found between Eco-enzyme and the combination treatment (p = 1.00). In conclusion, both Eco-enzyme and its combination with dishwashing soap effectively reduced E. coli on tablespoons. Future studies may explore various formulations and concentrations of Eco-enzymes for disinfecting other food utensils.